Microbiological and Analytical Evaluation of Semi-Solid Formulations of Doxycycline Hyclate under Accelerated Stability Conditions - Ola Aasi; Youssef Alahmad Alahmad; Mustafa Beesh; Amin Swed (مجلة بغداد للعلوم)
Doxycycline Hyclate (DOX) is a broad-spectrum antibiotic that belongs to the tetracycline family. It has been widely used in the treatment of several inflammatory diseases, and is considered the first-line therapy in the management of moderate to severe cases of acne. In this research, Doxycycline was formulated in four semi-solid formulations (F1and F2 as Gels, F3 and F4 as ointments), then these formulations were subjected to accelerated stability conditions for three months. The formulations were evaluated using microbiological and analytical methods after one and three months. Agar well diffusion method was used as a microbiological method to screen the antibacterial activity of semi-solid formulations against two types of bacteria, Staphylococcus Aureus and Pseudomonas Aeruginosa. HPLC was used as an analytical method for the quantitative and qualitative determination of these formulations. A comparison between a microbiological assay and analytical assay was achieved to evaluate the activity. The results showed that the ointment formulations were more stable than gel formulations since the percentages of drug were 91%, 93% at 25 ˚C after one month for formulations (F3, F4) against 90%,65% for formulations (F1, F2) respectively. Antibacterial activity results showed that formulation F4 had the highest zone of inhibition, which is 31mm for S.aurues and 26 mm for P. aeruginosa after storing it for three months at 25C°. The formulations were still effective despite the chemical degradation of doxycycline, this effectiveness returns to the fact that degradation products could still have active structural parts responsible for the antibacterial activity.